Factors Associated With New-Onset Seizures Following Stereotactic Radiosurgery for Newly Diagnosed Brain Metastases - Emily C. Lerner, BA; Ethan S. Srinivasan, BS; Gloria Broadwater, MS; Aden P. Haskell-Mendoza, MS; Ryan M. Edwards, BA; David Huie, MD; Eugene J. Vaios, MD, MBA; Scott R. Floyd, MD, PhD; Justus D. Adamson, PhD; Peter E. Fecci, MD, PhD (Advances in Radiation Oncology, 2022)
Purpose: Stereotactic radiosurgery (SRS) is a highly effective therapy for newly diagnosed brain metastases. Prophylactic antiepileptic drugs are no longer routinely used in current SRS practice, owing to a perceived low overall frequency of new-onset seizures and potential side effects of medications. It is nonetheless desirable to prevent unwanted side effects following SRS. Risk factors for new-onset seizures after SRS have not been well established. As such, we aimed to characterize variables associated with increased seizure risk. Methods and Materials: Patients treated with SRS for newly diagnosed brain metastases between 2013 and 2016 were retrospectively reviewed at a single institution. Data on baseline demographics, radiation parameters, and clinical courses were collected. Results: The cohort consisted of 305 patients treated with SRS without prior seizure history. Median age and baseline Karnofsky Performance Scale score were 64 years (interquartile range, 55-70) and 80 (interquartile range, 80-90), respectively. Twenty-six (8.5%) patients developed new-onset seizures within 3 months of SRS. There was no association between new-onset seizures and median baseline Karnofsky Performance Scale score, prior resection, or prior whole brain radiation therapy. There were significant differences in the combined total irradiated volume (12.5 vs 3.7 cm3, P < .001), maximum single lesion volume (8.8 vs 2.8 cm3, P = .003), lesion diameter (3.2 vs 2.0 cm, P = .003), and number of lesions treated (3 vs 1, P = .018) between patients with and without new-onset seizures, respectively. On multivariate logistic regression, total irradiated volume (odds ratio, 1.09 for every 1-cm1 increase in total volume; confidence interval, 1.02-1.17; P = .016) and pre-SRS neurologic symptoms (odds ratio, 3.08; 95% confidence interval, 1.19-7.99; P = .020) were both significantly correlated with odds of seizures following SRS. Conclusions: Our data suggest that larger total treatment volume and the presence of focal neurologic deficits at presentation are associated with new-onset seizures within 3 months of SRS. High-risk patients undergoing SRS may benefit from counseling or prophylactic antiseizure therapy.